2011
DOI: 10.1002/eji.201141760
|View full text |Cite
|
Sign up to set email alerts
|

NK cells can generate from precursors in the adult human liver

Abstract: Hepatic NK cells constitute $40% of hepatic lymphocytes and are phenotypically and functionally distinct from blood NK cells. Whether hepatic NK cells derive from precursors in the BM or develop locally from hepatic progenitors is still unknown. Here, we identify all five known sequential stages of NK-cell development in the adult human liver and demonstrate that CD34 1 hepatic progenitors can generate functional NK cells. While early NK-cell precursors (NKPs) were similar in liver and blood, hepatic stage 3 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 54 publications
(98 reference statements)
2
49
0
Order By: Relevance
“…The cNK cells generated from Lin − CD127 − IEL express granzyme B, can produce IFNγ and lyse classical NK cell targets, indicating that these two innate IEL subsets are closely related. In humans, NK cell precursors have so far been described in secondary lymphoid tissues like lymph nodes,50 tonsil,51 liver,52 in the uterus,53 the thymus54 and as CD117 + cells in the lamina propria of the intestine,55 but not in the intestinal epithelium. Thus, our results indicate that Lin − CD127 − IELs harbour precursors to NK and T cells, which may provide plasticity in response to environmental insults.…”
Section: Discussionmentioning
confidence: 99%
“…The cNK cells generated from Lin − CD127 − IEL express granzyme B, can produce IFNγ and lyse classical NK cell targets, indicating that these two innate IEL subsets are closely related. In humans, NK cell precursors have so far been described in secondary lymphoid tissues like lymph nodes,50 tonsil,51 liver,52 in the uterus,53 the thymus54 and as CD117 + cells in the lamina propria of the intestine,55 but not in the intestinal epithelium. Thus, our results indicate that Lin − CD127 − IELs harbour precursors to NK and T cells, which may provide plasticity in response to environmental insults.…”
Section: Discussionmentioning
confidence: 99%
“…These and many other findings are the basis of a large number of ongoing studies and clinical trials for NK cell immunotherapy against cancer (Miller, 2013). The current prevailing model suggests that adult BM is the primary site of NK cell development (Di Santo, 2006), although early lymphoid progenitors with NK lineage potential have been also identified in human tonsil (Freud et al, 2005), thymus (McClory et al, 2012;Res et al, 1996), and liver (Moroso et al, 2011), suggesting that some subsets of human NK cells develop extra medullary. Maturation of human NK cells is characterized by the loss of CD34 and C-KIT (CD117) expression , followed by sequential upregulation of CD94, CD16, and killer cell Ig-like receptors (KIR) , where the expression of the latter three receptors distinguishes NK cells from other members of ILC family.…”
Section: Introductionmentioning
confidence: 89%
“…1 NK cells develop from CD34 ϩ hematopoietic precursor cells, and it is generally accepted that bone marrow is the main site of NK cell development in adult humans. 1,2 However, several reports have shown that hematopoietic precursors and developing NK cells also can be found in human adult intestine, 3 uterus, 4,5 liver, 6 and secondary lymphoid tissues, such as lymph nodes and tonsils. 7 The thymus also is considered a site of NK cell development because mature NK cells and multipotent as well as bipotent T/NK and NK/dendritic cell (DC) precursors can be isolated from human postnatal thymus, but a complete pathway of NK cell differentiation at this site has not been defined in humans.…”
Section: Introductionmentioning
confidence: 99%